إدارة المخاطر في مشروعات نظم المعلومات - Ziad Mansour Ahmed (International Journal of Computers and Informatics, 2024)
This paper is concerned with studying the risks facing information systems projects in terms of identifying or defining risks, studying the most important of these risks and analyzing their causes, classifying risks into levels in terms of probability of occurrence and impacts of occurrence. This paper also discusses how to arrange risks and give them priorities, and how to plan to confront these risks. It also sheds light on the procedures that must be taken to conduct continuous analysis and monitoring of risks in a way that leads to avoiding them or mitigating their effects.
Keywords: Information systems projects; project management; risk management